Hubungan Antara Logika Matematika dengan Kecepatan dan Ketepatan Eksekusi Kode pada Mata Kuliah Alogaritma Pemprograman Universitas Sulawesi Barat Pendidikan Matematika Kelas 2025C - Nur Atita; Bungah Bungah; Lisma Lisma; Cindy Citra Mentari; Muh Albar; Ketrin Rinayanti Manullang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to explain how the relationship between mathematical logic with the speed and accuracy of code execution in the programming algorithm course at the University of West Sulawesi. Mathematical logic is a branch of mathematics that studies the basic principles of logical reasoning and methods for determining the truth of a statement. The method used in this study is a qualitative method with data collection through observations of the mathematical logic abilities of students at the University of West Sulawesi, Mathematics Education study program, class 2025 C. The results showed that most of the mathematics education students, class 2025 C, have mathematical logic abilities in the medium to high category which is influenced by the intensity of practice. Students with moderate to high mathematical logic abilities tend to be faster in executing code and completing programming tasks, while students with low logical abilities often experience difficulties in understanding programming concepts and flows. Thus, it can be concluded that there is a clear relationship between mathematical logic abilities and the speed and accuracy of code execution.